2017
DOI: 10.1111/jvh.12809
|View full text |Cite
|
Sign up to set email alerts
|

Community‐based screening of hepatitis C with a one‐step RNA detection algorithm from dried‐blood spots: Analysis of key populations in Barcelona, Spain

Abstract: Alternative strategies are required to enhance the diagnosis of silent hepatitis C virus (HCV) infections in key populations at risk. Among them, HCV prevalence and bio-behavioural data are scarce for HIV-negative men who have sex with men (MSM) and men and trans-women sex workers. We sought to describe and assess the potential benefits of a community-based one-step HCV screening and confirmatory strategy for these populations in Barcelona. The screening strategy based on a real-time RT-PCR assay for HCV-RNA d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
28
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 54 publications
5
28
0
1
Order By: Relevance
“…The median prevalence was 51.1% for anti-HCV antibodies (p25th = 24.3%; p75th = 64.3%) and 61.8% for HCV-RNA (p25th = 60.5%; p75th = 70.1%). Eleven studies provided information about HCV genotypes in infected individuals 9,24,32,36,37,40,41,4548 . Only 7 studies included the HIV/HCV coinfection status 24,28,29,31,37,38,47 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The median prevalence was 51.1% for anti-HCV antibodies (p25th = 24.3%; p75th = 64.3%) and 61.8% for HCV-RNA (p25th = 60.5%; p75th = 70.1%). Eleven studies provided information about HCV genotypes in infected individuals 9,24,32,36,37,40,41,4548 . Only 7 studies included the HIV/HCV coinfection status 24,28,29,31,37,38,47 .…”
Section: Resultsmentioning
confidence: 99%
“…39 NoGermanyTMA: VERSANT HCV RNA Qualitative Assay (Siemens)TMA: VERSANT HCV RNA Qualitative Assay (Siemens)150100100100 2018 Saludes et al . 45 1, 2, 3, 4NoSpainQuantiFast Pathogen RT-PCR + IC Kit (QIAGEN)Abbott RealTime HCV (Abbott Molecular)8238100100 2012 Santos et al . 44 NoBrazilIn-house qPCRIn-house qPCR1681019894.3 2002 Solmone et al .…”
Section: Resultsmentioning
confidence: 99%
“…DBS collection has been demonstrated to facilitate HCV testing and linkage to care in populations where standard phlebotomy is a barrier . The performance of HCV RNA testing on DBS samples has been shown to be diagnostically and clinically comparable to plasma across multiple molecular platforms . However, the literature is limited when evaluating DBS for HCVcAg testing.…”
Section: Discussionmentioning
confidence: 99%
“…While the good performance of HCV core antigen in plasma has been demonstrated, there are many settings for which the collection or transport of plasma to a central facility is not possible. Dried blood spot (DBS) utility as an alternative sample type in HCV serology and molecular testing (NAT) has been well documented . The major advantages of finger‐stick capillary DBS testing are as follows: (a) simplified collection with no need for phlebotomy (through self‐ or assisted‐collection); (b) easy and affordable transportation of samples (no cold chain transport requirement as samples are stable at room temperature (24°C), with HCV RNA and core antigen stable for a year or more allowing shipment through the mail) and (c) multiple sample availability; as up to five spots are collected, which allows for reflex testing if confirmation is required or multi‐analyte testing.…”
Section: Introductionmentioning
confidence: 99%
“…A generalised screening through dried blood spots in Barcelona did not detect any incident HCV in this subgroup. In contrast, highrisk behaviour and the incidence of other STIs suggested that periodic screening could be necessary in MSM [93]. Screening the specific subgroup with high-risk behaviour on PrEP is needed and is currently part of the reimbursement criteria for PrEP medication.…”
Section: People With High-risk Behaviourmentioning
confidence: 99%